2007
DOI: 10.1016/j.plefa.2007.10.013
|View full text |Cite
|
Sign up to set email alerts
|

An n-3 fatty acid deficient diet affects mouse spatial learning in the Barnes circular maze

Abstract: Our previous work demonstrated that a decrease in brain docosahexaenoic acid (DHA) in rodents was associated with poorer performance in the Morris water maze. In this study we showed a deficit in spatial task performance of n‐3 deficient rats using the Barnes circular maze, which is similar to the Morris maze in that both tests require an escape response. Deficiency has been accomplished through the use of a two generational model in which the dam is deprived of n‐3 fatty acid sources and her offspring are the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 26 publications
0
44
0
Order By: Relevance
“…Beyond conferring membrane fluidity, DHA and EPA are used continuously for the biogenesis and maintenance of neuronal membranes, and associated with many physiological functions, such as learning and memory. [8][9][10] Both DHA and EPA are structurally intermingled with larger phospholipid molecules in the neuronal membrane, in particular aminophospholipids, such as phosphatidylserine and phosphatidylethanolamine. Our group and others have demonstrated that supplementation with n-3 PUFAs, especially DHA, robustly reduces the extent of neuronal damage and neurological deficits after neonatal H/I 11 and adult cerebral ischemia.…”
Section: Strokementioning
confidence: 99%
“…Beyond conferring membrane fluidity, DHA and EPA are used continuously for the biogenesis and maintenance of neuronal membranes, and associated with many physiological functions, such as learning and memory. [8][9][10] Both DHA and EPA are structurally intermingled with larger phospholipid molecules in the neuronal membrane, in particular aminophospholipids, such as phosphatidylserine and phosphatidylethanolamine. Our group and others have demonstrated that supplementation with n-3 PUFAs, especially DHA, robustly reduces the extent of neuronal damage and neurological deficits after neonatal H/I 11 and adult cerebral ischemia.…”
Section: Strokementioning
confidence: 99%
“…Because of the increased demand, sufficient supply of the essential PUFAs and proper ratio of AA to DHA particularly during early life is critical for proper development and function of the nervous system [16,31,[55][56][57][58][59] . Both human and animal studies have correlated the presence of AA and DHA during critical period of development to enhanced visual, cognitive and motor functions [23, [60][61][62][63] . A link between imbalances in the AA to DHA composition and abnormalities of fatty acid metabolism have been shown to play a role in the pathology of various psychiatric disorders, including attention deficit hyperactivity disorder, dyslexia, dyspraxia, bipolar disorder and schizophrenia [51,[64][65][66][67][68][69][70][71] .…”
Section: Dietary Lipid Imbalances In Asdsmentioning
confidence: 99%
“…Clinical evidence indicates that term infants given formula supplemented with either DHA plus arachidonic acid or DHA alone have substantially better visual acuity (3) and improved cognitive ability (4). Animal studies revealed that deficiency of DHA resulted in a poorer performance on cognitive and behavioral tests whereas supplementation with DHA led to recovery of learning and memory-related performance (5). Furthermore, neurodegeneration and neuropsychiatric disorders are related to a low level of DHA, and supplementation with DHA ameliorated the symptoms (6).…”
mentioning
confidence: 99%